2011
DOI: 10.1055/s-0031-1300093
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant Activity of Some Antileprotic Drugs

Abstract: DPPH (alpha,alpha-diphenyl-beta-picryl hydrazyl) (CAS 217-591-8), a stable free radical can be used to determine the antioxidant activity (AOA) of some drugs. In the present study the DPPH method was used for the first time to test AOA of dapsone (CAS 80-08-0), clofazimine (CAS 2030-63-9) and rifampicin (CAS 13282-42-1) in vitro and deproteinated blood method. Ascorbic acid (CAS 50-81-7) was used as a control in the study, which showed concentration-dependent antioxidant activity. Rifampicin showed a per se ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Experimental and clinical studies on hypertension suggest that increased production of reactive oxygen species plays a role in its etiology [1], and epidemiological studies indicate that a dietary intake of ascorbic acid (CAS 50-81-7), an antioxidant [2,3], reduces the incidence of hypertension [4,5]. These findings suggest that ascorbic acid lowers blood pressure (BP) in patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and clinical studies on hypertension suggest that increased production of reactive oxygen species plays a role in its etiology [1], and epidemiological studies indicate that a dietary intake of ascorbic acid (CAS 50-81-7), an antioxidant [2,3], reduces the incidence of hypertension [4,5]. These findings suggest that ascorbic acid lowers blood pressure (BP) in patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that in the presence of rifampicin, the concentration of DPPH peaks decreased depending on the concentration. Furthermore, the free radical scavenging activity of rifampicin is measured by Kalpana et al [ 15 ] and ascorbic acid was used for comparison. Although the above-mentioned researchers used different procedures, the results of this work are consistent with the available literature.…”
Section: Resultsmentioning
confidence: 99%